State of the art of coronary computed tomography angiography. Issue 2 (May 2020) - El Merhi, F.; Bou-Fakhredin, R.; El Ashkar, B.; Ghieh, D.; Ghosn, Y.; Saade, C.
Abstract: Objectives: The aim of this paper is to evaluate contrast media (CM) bolus geometry and opacification patterns in the coronary arteries with particular focus on patient, scanner and safety considerations during coronary computed tomography angiography (CCTA). Key findings: The rapid evolution of computed tomography (CT) technology has seen this imaging modality challenge conventional coronary angiography in the evaluation of coronary artery disease. Increases in spatial and temporal resolutions have enabled CCTA to become the modality of choice when evaluating the coronary vascular tree as an alternative in the diagnostic algorithm for acute chest pain. However, these new technologic improvements in scanner technology have imposed new challenges for the optimisation of CM delivery and image acquisition strategies. Conclusion: Understanding basic CM-imaging principles is essential for designing optimal injection protocols according to each specific clinical scenario, independently of scanner technology. Implications for practice: With rapid advances in CT scanner technology including faster scan acquisitions, the risk of poor opacification of coronary vasculature increases significantly. Therefore, awareness of CM delivery protocols is paramount to consistently provide optimal image quality at a low radiation dose.